Microplastic removal in aquatic systems using extracellular polymeric substances (EPS) of microalgae - H. Hadiyanto; Adian Khoironi; Inggar Dianratri; Falvocha Alifsmara Joelyna; Marcelinus Christwardana; Adhelia Intan Sabhira; Rifqi Ahmad Baihaqi (Sustainable Environment)
Microplastic contamination in clean water sources and household wastewater is a significant environmental issue that requires sustainable remediation solutions. This study aims to evaluate the effectiveness of extracellular polymeric substances (EPS) produced by different microalgae strains in removing microplastics from aquatic environments. Four microalgae strains, namely Spirulina sp. Tetraselmis chuii, Chlorella vulgaris, and Dunaliella salina, were cultivated under stress conditions, including the application of polypropylene microplastics, increased light intensity, and enhanced nutrient levels, to stimulate EPS production. The EPS produced was then interacted with microplastics to form hetero-aggregates. Spirulina sp. produced the highest amount of EPS (4.59 g), followed by Tetraselmis chuii (3.27 g), Chlorella vulgaris (3.03 g), and Dunaliella salina (2.86 g). The carbohydrate content in dry EPS was also highest in Spirulina sp. (0.21%), with Tetraselmis chuii (0.19%), Chlorella vulgaris (0.16%), and Dunaliella salina (0.11%) following. The microplastic flocculation efficiency mirrored these results, with Spirulina sp. flocculating 1.397 g of microplastics, outperforming the other strains. These findings suggest that Spirulina sp. and Tetraselmis chuii are particularly effective in producing EPS that can be utilized to remove microplastics from aquatic environments, offering a promising eco-friendly solution.